Konsep Etika dalam Berkeluarga, Bermasyarakat dan Berpolitik Perspektif Penafsiran Alqur'an - Silvi Vadila Putri; Alifa Rafli Akbar; Ali Asman; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study discusses the key concepts in Islamic teachings related to social and political ethics, including hospitality, silaturahmi (maintaining family ties), amanah (trustworthiness), and justice, referring to verses from the Qur'an and the hadith of Prophet Muhammad sallallāhu ‘alaihi wa sallam. The concept of hospitality is emphasized as a positive attitude towards guests and maintaining family relationships, which should be preserved even in cases of severed ties. Furthermore, the importance of silaturahmi in Islam is also a focus, where treating relatives well and maintaining good relations is an obligation, as reflected in the teachings of the Prophet. In the aspect of amanah, Islam teaches that every individual, especially leaders and judges, must carry out their duties with responsibility, honesty, and integrity to establish justice in society. The concept of justice is also discussed in QS. An-Nisa' (4:58), which emphasizes that fair decisions must be made according to the applicable norms and ethics. According to Quraish Shihab in his book Wawasan Al-Qur’an, politics in Islam involves not only legal decisions but also incorporates principles of justice and ethics that must be applied by every leader or judge. Overall, this research shows that integrity, ethics, and justice are fundamental values in Islam that must be applied in social and political life to create a just, peaceful, and prosperous society.